Laparoscopic nephroureterectomy is associated with higher risk of adverse events compared to laparoscopic radical nephrectomy - Bastiampillai, Ravin; Lavallée, Luke T.; Cnossen, Sonya; Witiuk, Kelsey; Mallick, Ranjeeta; Fergusson, Dean A.; Schramm, David; Morash, Chris; Cagiannos, Ilias; Breau, Rodney (Canadian Urological Association Journal, 2016)
Background: Laparoscopic radical nephrectomy (LRN) and laparoscopic nephroureterectomy (LNU) are similar procedures and some surgeons may counsel both patients groups the same regarding peri-operative risks. The objective of this study is to compare complications following LRN and LNU. Patients and methods: A historical cohort of patients who received LRN or LNU between 2006 and 2012 was reviewed from the National Surgical Quality Improvement Program (NSQIP) database. Patient and surgical characteristics, and outcomes up to 30-days post-operative were abstracted. Univariable and multivariable associations between procedure (LRN or LNU) and any adverse event were determined. Results: During the study period, 4904 patients met inclusion criteria. Of these, 4159 (85%) received a LRN while 745 (15%) received a LNU. LNU was associated with more complications than LRN (21% vs. 12%, respectively, p-value <0.01). The most common complications for LNU vs. LRN, respectively, were: bleeding requiring blood transfusion (9.0% vs. 6.0%), urinary tract infection (4.6% vs. 1.5%), wound infection (1.3% vs. 1.8%), and unplanned intubation (2.3% vs. 0.9%). On multivariable analysis, LNU was associated with higher risk of any complication compared to LRN (RR 1.41, 95% CI 1.16-1.72). Conclusions: Post-operative complications within 30 days of surgery are common after LNU and LRN. Despite having technical similarities, LNU carries a significantly higher risk of short-term complications compared to LRN. This information should be considered when counseling patients prior to surgery.